Ventricular-arterial coupling in hypertensive patients after TAVR. It is not all about the valve. (14th October 2021) - Islas, F; Bottino, R; Jimenez, P; Nombela, L; Marcos Alberca, P; D'Amato, M; Lepori, A; Olmos, C; Perez De Isla, L; De Agustin, A
Abstract: Background: In severe aortic stenosis, the left ventricle faces the challenge of the valvular load and the arterial load caused by abnormalities in systemic arterial compliance and systemic vascular resistance. The aim of this study is to assess the effect of hypertension control on left ventricular performance in patients that underwent TAVR. Methods: 68 consecutive patients who underwent TAVR were analyzed; all patients were evaluated to confirm severe aortic stenosis with transthoracic echo (TTE). Conventional echo parameters were assessed as well as left ventricular mechanics parameters and vascular parameters such as arterial elastance (Ea), ventricular elastance (Ees) and V/Ac; besides all patients underwent TTE prior to TAVR, at discharge and 90 days follow-up visit. Results: Mean age was 82±5; mean aortic valve area was 0.69±0.19, mean left ventricular ejection fraction was 58.3±12.1 and mean ventricular-arterial coupling was 1.6±0.9. At 90 days follow up we observed a significant worsening in V/Ac in those patients with poor control of blood pressure (>140/90mmHg), (1.8±0.5 vs 2.1±0.3, p=0.03). Aortic impedance was significantly higher (4.4±1.4 vs 3.5±1.2, p=0.05); Ea and Ees were also significantly higher in hypertensive patients (2.3±0.8 vs 1.7±0.6, p=0.05) and (1.4±0.7 vs 0.9±0.6, p=0.01) respectively. Left ventricular ejection fraction (LVEF) and global longitudinal strain (GLS) showed a slightly reduction in hypertensive patients, although not statistically significant. Conclusions: Control of blood pressure seems to be an important factor that contributes to a better or rather worse LV performance and could have a potential role in systolic function and clinical outcome of patients after TAVR. Funding Acknowledgement: Type of funding sources: None.